Endogenous price leadership: A theoretical and experimental analysis - Werner Güth; Kerstin Pull; Manfred Stadler; Alexandra Zaby (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
We present a model of price leadership on homogeneous product markets where the price leader is selected endogenously. The price leader sets and guarantees a sales price to which followers can adjust according to their individual supply functions. The price leader then clears the market by serving the residual demand. Firms with different marginal costs would induce different prices if they were price leaders. Somewhat counter-intuitively, lower marginal costs of the leader imply higher prices. We compare two mechanisms to determine the price leader in a between-subjects design, majority voting and competitive bidding. The experimental data of later rounds support our theoretical finding that experienced price leaders with lower marginal costs choose higher prices. In the majority voting treatment, participants with higher marginal costs more often establish the lowest cost competitor as price leader in order to induce a higher sales price.
Keywords: D43; D74; L11; 330; bidding; experimental economics; majority voting; price leadership